(untitled) (Research, Society and Development, 2022)
In grain production, the extensive use of fungicides and the effects on new genetically modified materials are of concern with respect to final quality. The objective of this study was to evaluate qualitative aspects of Intacta soybeans, as a function of foliar fungicide application. The experiment was conducted in the northern region of Mato Grosso. The experimental design was in randomized blocks in a 5 x 8 factorial scheme, with 5 fungicide systems and 8 cultivars of Intacta soybeans, in three repetitions. The apparent specific mass, unitary and thousand-grain masses were evaluated by variance analysis and Tukey’s test (5%), and the fungal incidence, descriptively. The evaluated results varied according to the combination of fungicides applied, but the values of the physical properties remained above the ones verified in the region. For apparent specific mass, the treatment that stood out the most was T1 (Prothioconazole+Trifloxystrobin), for unit-specific mass the best results were observed with the use of T4 (Fluxapiroxad+Pyraclostrobin) and for the mass of 1,000 grains, the treatment with the best results was T3 (Picoxystrobin+Cyproconazole). The grains showed better sanitary quality with the application of the fungicide systems Prothioconazole+Trifloxystrobin and; Picoxystrobin+Cyproconazole. The lowest incidence of fungus was observed for the cultivar CD2750.